Uma análise estilística da língua brasileira de sinais: Variações de seu uso no processo interativo - Delgado, Isabelle Cahino (2012)
This thesis aims at analyzing the stylistic aspects of Brazilian sign language in use in the cities of Recife and João Pessoa, considering its variable feature in a sociolinguistic context. We assume that the sociolinguistic variation is a means through which the social is incorporated into the language and therefore the nature of social meaning is valued. Thus, variation becomes meaningful. In methodological procedures we consider that it is a documentary research, which made use of a database project entitled Preliminary Studies for the National Inventory of Linguistic Diversity - The Brazilian Sign Language in the Northeast: the variants of João Pessoa and Recife. The analysis and discussion of the results were developed with the support of the software ELAN, a relevant tool for the transcription and analysis of data. At first, sociointeractionist analysis with 96 (ninety-six) users of LIBRAS was done, 54 (fifty four) living in Joao Pessoa and 42 (forty-two) in Recife. As a second step, from the 200 recorded signals in the Swadesh list, we chose five of them that showed a large lexical variation for analysis with ELAN: WHITE, HUSBAND, WIFE, CHILD and PERSON. The third moment was devoted to the study of the dialect in the community, that is, how these signals now are used in the context of informal interaction and communication. As research results we can consider: where and how the language circulates among its users, as well as its purpose, relevance, age and place of acquisition / learning, the interpreter’s needs in the contexts of social interaction, the (in) existence of instructional material, cultural groups and cultural material in LIBRAS, its fluency in everyday life and language difficulties with its user. In the analysis focused on style, we analyzed aspects that are particular of LIBRAS, such as configuration parameters of the hand, point of articulation, movement, orientation and facial and body expressions, considering the dialectal variation between towns (João Pessoa and Recife), as well as the dialect in the community in practice, in the context of use by subjects. Finally, we described and analyzed the variants, from an informal to a formal condition of annunciation and thus we valued the unique style that LIBRAS evidences, which assures that even as a signaled language it is full of indexical prints and value in the Sociolinguistics field.